2006
DOI: 10.1007/s00412-005-0044-2
|View full text |Cite
|
Sign up to set email alerts
|

The SuUR gene influences the distribution of heterochromatic proteins HP1 and SU(VAR)3–9 on nurse cell polytene chromosomes of Drosophila melanogaster

Abstract: We have investigated the distribution of three heterochromatic proteins [SUppressor of UnderReplication (SUUR), heterochromatin protein 1 (HP1), and SU(VAR)3-9] in chromosomes of nurse cells (NCs) and have compared the data obtained with the distribution of the same proteins in salivary gland (SG) chromosomes. In NC chromosomes, the SU(VAR)3-9 protein was found in pericentric heterochromatin and at 223 sites on euchromatic arms, while in SG chromosomes, it was mainly restricted to the chromocenter. In NC chrom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 62 publications
0
17
0
Order By: Relevance
“…Interestingly, however, embryonic stem cells lacking the SUV39H1 and SUV39H2 H3K9 methyltransferases showed delayed replication timing of centromeric repeats (Jorgensen et al 2007), underscoring the context dependency of the interaction between chromatin and the replication timing program. Studies of endoreplication of Drosophila polytene chromosomes have suggested a role for HP1 in the maintenance of underreplicated regions in connection with the SuUR protein (Makunin et al 2002;Koryakov et al 2006;Pindyurin et al 2007Pindyurin et al , 2008. It has been suggested that open chromatin plays a role in replication initiation (Aggarwal and Calvi 2004;Goren et al 2008;Schwaiger et al 2009;Hansen et al 2010;Macalpine et al 2010).…”
Section: Replication Timing Of Centromeric Repeats Is Advanced After mentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, however, embryonic stem cells lacking the SUV39H1 and SUV39H2 H3K9 methyltransferases showed delayed replication timing of centromeric repeats (Jorgensen et al 2007), underscoring the context dependency of the interaction between chromatin and the replication timing program. Studies of endoreplication of Drosophila polytene chromosomes have suggested a role for HP1 in the maintenance of underreplicated regions in connection with the SuUR protein (Makunin et al 2002;Koryakov et al 2006;Pindyurin et al 2007Pindyurin et al , 2008. It has been suggested that open chromatin plays a role in replication initiation (Aggarwal and Calvi 2004;Goren et al 2008;Schwaiger et al 2009;Hansen et al 2010;Macalpine et al 2010).…”
Section: Replication Timing Of Centromeric Repeats Is Advanced After mentioning
confidence: 99%
“…Interestingly, in Drosophila polytene chromosomes and Kc cells, HP1 target regions often overlap with regions bound by the Suppressor of Underreplication (SuUR) protein (Koryakov et al 2006;Pindyurin et al 2007). SuUR binds to underreplicated and late replicating regions on Drosophila polytene chromosomes (Makunin et al 2002) and to late replicating regions in Kc cells (Pindyurin et al 2007).…”
mentioning
confidence: 99%
“…Overall, in contrast to SGs (Zhimulev et al 1982), the frequency of chromosome breaks in NCs is remarkably low (Koryakov et al 2006). Of 42 such regions, only 24 correspond to late replication sites (Fig.…”
Section: Regions Of Late Replicationmentioning
confidence: 90%
“…To compare positions of late-replicating regions and regions associated with SUUR, the data published previously were used (Koryakov et al 2006). We revised the list of SUURpositive chromosomal sites, and added several regions…”
Section: Regions Of Late Replicationmentioning
confidence: 99%
See 1 more Smart Citation